Tutorat en ligne – Analyse des pratiques d'interaction et de feedback dans un blogue pour l'apprentissage de l'anglais - Annick Rivens Mompean (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Blogs can be used in a teaching/learning situation and research has shown the motivational value of this kind of practice for the development of written productions, in a socio-constructivist setting, due to the involvement of the learners in social and meaningful activities. This leads to the question of correction and feedback from the tutor and his role throughout the interactions. A qualitative analysis of the interactions defines the way the tutor finds his place in the online exchanges, in the comments. We examine some of the parameters that seem to determine his role as an online tutor who is not only a language corrector but also a facilitator, a member of the debating community, engaged in a nearly symmetrical relationship with the learners. These elements enable us to understand what are the constitutive elements of successful coaching systems that reorganize the roles of the different actors and modify the way the pedagogical communication takes place online.